Ruled translating solitons in Minkowski 3-space - Aydin, Muhittin Evren; Lopez, Rafael (Elsevier, 2021)
We characterize all ruled translating solitons in Minkowski 3-space. In contrast to the Euclidean space, we find ruled translating solitons that are not cylindrical. These surfaces appear when the vector field that defines the rulings, viewed as a curve, is a lightlike straight line. We also classify all cylindrical translating solitons, obtaining surfaces that can be considered as analogous to the grim reapers of Euclidean space, but also other surfaces which have no counterpart in the Euclidean space. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Ruled surface; Translating soliton; Minkowski space; Grim reaper